EMPOWERING KAMPUNG PEROS: A COLLABORATIVE ART-BASED SULAM PROJECT FOR SUSTAINABLE TOURISM - Noorhaslina, Senin; Candida, Jau Emang; Doris, Maying; Aliffazraie, Jali; Hishamuddin, Siri; Asrul Asshadi, Mohamad Morni; Amir Hassan, Mohd Shah (2025)
This SULAM project highlights how a collaborative arts and digital storytelling initiative empowered the community of Kampung Peros located within the Sarawak Delta Geopark to promote sustainable tourism. By merging creative disciplines such as mural design, documentary filmmaking, and digital marketing, the project increased the village’s visibility, enhanced cultural preservation, and built the digital and creative capacities of local residents. This community-led transformation has contributed to new economic opportunities, revitalized cultural pride, and aligned with national and global goals for sustainable development.